A CHECK LIST OF BLOW FLIES (DIPTERA : CALLIPHORIDAE) FROM NORTH-WEST OF INDIA - SINGH, DEVINDER; SIDHU, INDERPAL. SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
A check list of blow flies from north-west of India is provided. The study area comprises the states of Punjab, Haryana, Chandigarh, Himachal Pradesh, Uttaranchal, Jammu & Kashmir, Delhi and Rajasthan. Forty-nine species referable to 22 genera under the subfamilies Caliphorinae, Ameniinae, Rhininae, Helicoboscinae and Chrysomyinae are included in this list.